2017
DOI: 10.1038/nature22071
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome landscapes of major melanoma subtypes

Abstract: Melanoma of the skin is a common cancer only in Europeans, whereas it arises in internal body surfaces (mucosal sites) and on the hands and feet (acral sites) in people throughout the world. Here we report analysis of whole-genome sequences from cutaneous, acral and mucosal subtypes of melanoma. The heavily mutated landscape of coding and non-coding mutations in cutaneous melanoma resolved novel signatures of mutagenesis attributable to ultraviolet radiation. However, acral and mucosal melanomas were dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

103
1,420
11
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,115 publications
(1,635 citation statements)
references
References 54 publications
103
1,420
11
18
Order By: Relevance
“…Large-scale sequencing of both DNA and RNA of acral melanoma samples in future may help to provide unabridged molecular profile for acral melanoma and may contribute to resolve the question why acral melanoma cells do not respond equally and effectively to CDK4/6 inhibitors. Recently, a large, high-coverage wholegenome sequencing study of 183 cases of melanomas with differential subtypes (including 35 acral melanomas) is published, proving an excellent profile for genetic aberrations in acral melanoma (46). The data showed that acral and mucosal melanomas were dominated by structural changes and mutation signatures of unknown etiology, and they also found that greater proportions of the acral and mucosal melanoma genomes showed CNV than in cutaneous melanomas.…”
Section: Ink4amentioning
confidence: 89%
“…Large-scale sequencing of both DNA and RNA of acral melanoma samples in future may help to provide unabridged molecular profile for acral melanoma and may contribute to resolve the question why acral melanoma cells do not respond equally and effectively to CDK4/6 inhibitors. Recently, a large, high-coverage wholegenome sequencing study of 183 cases of melanomas with differential subtypes (including 35 acral melanomas) is published, proving an excellent profile for genetic aberrations in acral melanoma (46). The data showed that acral and mucosal melanomas were dominated by structural changes and mutation signatures of unknown etiology, and they also found that greater proportions of the acral and mucosal melanoma genomes showed CNV than in cutaneous melanomas.…”
Section: Ink4amentioning
confidence: 89%
“…While establishing the clonal structure of tumors is very important for predicting its evolution (Rosenthal et al, 2017), the detection of very early cancer stages will depend on the examination of healthy samples and will allow the definition of molecular hallmarks of premalignant conditions (Ryan and Faupel-Badger, 2016), and even the foreseen achievement of a precancer genome atlas (Campbell et al, 2016;Kensler et al, 2016). Examples are already available, for instance with a series of recent studies centered on melanoma: one in which mutations were examined from precursor to invasive lesions (Shain et al, 2015), another in which single-cell RNA-Seq was employed to profile a multitude of cell types (Tirosh et al, 2016), and then one focusing on subtypes from multiple sites (Hayward et al, 2017).…”
Section: Cancer Preventionmentioning
confidence: 99%
“…Acral and mucosal melanomas often lack a UVR mutational signature but harbour alternate mutational signatures not commonly identified in cutaneous melanoma [40]. Furthermore, approximately 50% of acral and mucosal melanomas lacked BRAF , RAS or NF1 mutations (i.e., triple-WT) but loss-of-function mutations in CDKN2A , TP53 and ARID2 , and activating hotspot mutations in GNAQ and SF3B1, were more common [40]. …”
Section: Somatic Alterations In Melanocytic Proliferationsmentioning
confidence: 99%
“…In contrast to cutaneous melanoma, acral and mucosal melanomas demonstrate a markedly different genomic landscape with a lower mutation burden dominated by large-scale copy number aberrations and structural rearrangements [40]. Acral and mucosal melanomas often lack a UVR mutational signature but harbour alternate mutational signatures not commonly identified in cutaneous melanoma [40].…”
Section: Somatic Alterations In Melanocytic Proliferationsmentioning
confidence: 99%
See 1 more Smart Citation